Concevoir l’espace domestique pour contrôler la main-d’œuvre : l’action de la Société mulhousienne des cités ouvrières durant la seconde moitié du XIXe siècle - Lucie Prohin (Amnis)
Founded on June 10, 1853, on the initiative of several industrialists, the Société mulhousienne des cités ouvrières (Mulhouse Workers' Housing Company) built more than a thousand homes until 1897. Housing part of the city’s workforce, these dwellings more broadly contributed to a paternalistic enterprise aiming at the moral improvement of the working classes. This study examines the spatial and economic devices designed to control the workers within their own domestic space. It thus questions the choice of individual housing, the role of the gardens attached to the houses, and the creation of a rent-purchase system. It also considers the operating mechanisms of this control, focusing on the selection-regulation-incentive triptych. Although the lived reality of the cités ouvrières remains challenging to grasp, the analysis shows the limited effectiveness of the control measures, and it underlines the ideological evolution of the project of the Mulhouse manufacturers during the second half of the 19th century.